Improved Quasi-Steady-State-Approximation Methods for Atmospheric Chemistry Integration - Jay, L. O.; Sandu, A.; Potra, F. A.; Carmichael, G. R. (SIAM journal on scientific computing, 1997)
In the last fifteen years the quasi-steady-state-approximation (QSSA) method has been a commonly used method for integrating stiff ordinary differential equations arising from atmospheric chemistry problems. In this paper a theoretical analysis of the QSSA method is developed, stressing its strengths and its weaknesses. This theory leads to practical improvements to the QSSA method. New algorithms, including symmetric and extrapolated QSSA are presented.